Company valuation: How to deal with a range of values? - Wiktor Patena (e-Finanse: Financial Internet Quarterly, 2011)
Company valuation is not done after having generated a few values being a result of applying different valuation methods. In many cases institutions ordering the valuation request a value which can be an equivalent of a market, transactional value. Often the one method (and the valuation resulting from the method) can be indicated, since the valuer claims that it gives the most precise value of the company. However, it is safer to consider the range of values and then try to determine the final value which is the result of a combination of several methods. However, the question is how to consistently deal with a range of values. One of the solutions are so-called mixed methods of company valuation. They are criticized in this paper as they are too subjective. Instead we suggest considering a portfolio approach PATEV (Portfolio Approach to Equity Valuation). In addition to having to choose a method of defining one value, the value is subject to further corrections: liquidity and control discounts.
Keywords: G32; C53; G12; 330; company valuation; range of values; liquidity discounts